Bolted shear connectors performance in self-compacting concrete integrated with cold-formed steel section - Lawan, Mustapha Muhammad (Brazilian Association of Computational Mechanics, 2016)
In conventional composite construction involving hot-rolled steel section, the composite action is usually achieved by using conventional headed shear studs connectors. However, use of headed studs is not practical for cold-formed steel (CFS) section due to its very thin form that is difficult to weld. A suitable bolt and nut type shear connector was proposed; experimental tests were carried out to evaluate its performance. This study also investigated the use of Self-Compacting Concrete (SCC) integrated with CFS by means of bolted shear connectors to develop composite action. Therefore, the objective of this paper was to investigate the performance of bolted shear connectors in SCC integrated with CFS section as composite beam system. Eighteen push-out test specimens comprising of M12, M14 and M16 sized bolted shear connector of grade 8.8 with longitudinal spacings of 150 mm, 250 mm and 300 mm centers were fabricated, cast and tested until failure. The experimental results showed that all bolted shear connectors possessed a good shear resistance capacity. Not much difference in strength capacity of specimens with M14 and M16 bolted shear connectors was found, perhaps due to CFS failure. Varying the size and longitudinal spacing of the bolted shear connectors revealed that the connectors’ strength capacity changed slightly between M14 and M16 bolts specimens but, significantly for M12 bolt specimens.